The Regulation of Songs and Their Relationship to Recreation and Entertainment According to Islamic Sharia (Islamic Sciences Journal, 2023)
In essence the worship of Allah Almighty aims at refining the human soul and elevating it to perfection, but not depriving it. The philosophy of recreation and entertainment is governed by the rules of Islam based on "respecting time, investing it in what is beneficial, and exploiting it properly without tampering or loss." The characteristics of recreation and entertainment in Islam are; slavery to  Allah  Almighty, and making a balance in the different aspects of the human soul. Recreation have great purposes, including: renewal of activity, removing tension, showing the tolerance of Islam, strengthening the means of social communication, and achieving emotional and psychological balance. They bring pleasure and fun to the souls of practitioners.